THE EFFECT OF INDUSTRIAL SECTOR GROWTH RATE, INVESTMENT AND WAGES ON LABOR ABSORPTION IN INDONESIA - Wati, Sintia; Juanda, Reza (LPPM Universitas Malikussaleh, 2024)
The purpose of this study was to determine how much influence the Growth Rate Of The Industrial Sector, Investment And Wage On Employment In Indonesia. This study uses a panel data approach from 2018 to 2022 in 34 Provinces in Indonesia. This study uses a combination of Cross-Section data with Time Series with the help of Eviews 10. From testing the selected panel model, namely the Random Effect Model (REM), the results show that the Growth Rate Of The Industrial Sector partially has a positive and insignificant effect on Employment In 34 Provinces in Indonesia, partially Investment has a negative and insignificant effect on Employment In 34 Provinces in Indonesia and the variable allocation of funds, partially wages have a negative and significant effect on Employment In 34 Provinces in Indonesia. The test results simultaneously state that the variable Growth Rate Of The Industrial Sector, Investment and Wage have a significant effect on Employment In 34 Provinces in Indonesia.